Clinical efficacy and safety of ruxolitinib in the management of myelofibrosis: A single institution experience in Taiwan. Issue 1 (2nd January 2016) - Chen, Yi-Yang; Huang, Cih-En; Lee, Kuan-Der; Chen, Chih-Cheng
Abstract : Objective : Myelofibrosis (MF) is a pathologic entity of myeloproliferative neoplasm (MPN) characterized by bone marrow fibrosis, extramedullary hematopoiesis, splenomegaly, and constitutional symptoms that severely affect the quality of life accompanied with the risk of leukemia development. Conventional treatment is usually ineffective and has limited impact on prolongation of survival. Dysregulated Janus kinase (JAK) signaling is common in MPN. In two randomized controlled trials, ruxolitinib, a potent pan-JAK inhibitor, has been shown to be highly effective in patients with intermediate- and high-risk MF. Method : We retrospectively analyzed the therapeutic outcome of 10 MF patients treated with ruxolitinib in our institute. Basic clinical data, JAK2 V617F mutational status and Myelofibrosis Symptoms Assessment Form (MF-SAF) to evaluate disease-related symptoms were recorded initially, and at every visit. Result : Among these patients, only half of the patients harbored JAK2 V617F mutation. After treatment with ruxolitinib, all patients had reduction of splenic size and reached nadir by week 24. Nine patients had body weight increment, and four of them had body weight increment more than 10%. Seven patients had their total symptom score reduced by more than 50% after therapy. The efficacy of ruxolitinib was irrelevant to JAK2 V617F mutational status. Adverse events were mainly hematological and easily manageable. Discussion and conclusion : Ruxolitinib is both safe and efficacious in a cohort of Asian patients with MF. The efficacy of ruxolitinib is irrelevant to the mutational status of JAK2 V617F